Nanosystems in Cardiovascular Medicine: Advancements, Applications, and Future Perspectives - Hossein Omidian; Niloofar Babanejad; Luigi X. Cubeddu (MDPI AG, 2023)
Cardiovascular diseases (CVDs) remain a leading cause of morbidity and mortality globally. Despite significant advancements in the development of pharmacological therapies, the challenges of targeted drug delivery to the cardiovascular system persist. Innovative drug-delivery systems have been developed to address these challenges and improve therapeutic outcomes in CVDs. This comprehensive review examines various drug delivery strategies and their efficacy in addressing CVDs. Polymeric nanoparticles, liposomes, microparticles, and dendrimers are among the drug-delivery systems investigated in preclinical and clinical studies. Specific strategies for targeted drug delivery, such as magnetic nanoparticles and porous stent surfaces, are also discussed. This review highlights the potential of innovative drug-delivery systems as effective strategies for the treatment of CVDs.